Frullania partita sp. nov. (Frullaniaceae, Porellales), a new leafy liverwort from the mid-Cretaceous of Myanmar. (April 2020) - Li, Ya; Wang, Yong-Dong; Schneider, Harald; Wu, Peng-Cheng
Abstract: Porellales is a predominantly epiphytic order of leafy liverworts. Recent relaxed molecular clock based studies introduced the hypothesis that the diversity of these liverworts expanded during the Cretaceous Terrestrial Revolution (KTR) period around 125–80 Ma. Until now, the fossil record provides only insufficient support to elucidate this hypothesis. Here, we describe a new inclusion of Porellales within mid-Cretaceous Burmese amber as Frullania partita sp. nov. (Frullaniaceae). It is characterized by apically apiculate leaf lobes, helmet-shaped to campanulate water sacs situated in some distance to stem, lanceolate styli, and apically deeply bilobed underleaves carrying rhizoid bundles in their basal parts. This new discovery contributes our understandings for the diversity aspects of Frullaniaceae (Porellales) of Burmese amber inclusions. The bark fragments connected to the branch provide the evidence that the fossil was an epiphyte.